Faktor Yang Mempengaruhi Tingkat Pengangguran di Beberapa Negara ASEAN - Ghifari Dimas Bayu Patra; Ida Nuraini; Muhammad Khoirul Fuddin (Program Studi Ekonomi Pembangunan, 2022)
This study aims to determine the effect of economic growth, population and inflation on unemployment rates in five ASEAN countries. This study uses a quantitative approach method. The data analysis tool used is multiple linear regression analysis using panel data through the help of Software Eviews 9. The results of this study indicate that partially, the economic growth variabel has a negative and significant effect on unemployment, the population variabel has a negative and significant effect on unemployment. Inflation has a positive and significant effect on unemployment. Simultaneously, economic growth, population and inflation have a positive and significant impact on unemployment in five ASEAN countries in 2009-2020.